Grinding effect on levofloxacin hemihydrate - Pereira, Rafael Nicolay (2015)
The grinding techniques were used in different pharmacotechnical process. The control of the effect of grinding in solid state properties of drugs is very important, mainly in hydrated drugs. Levofloxacin hemihydrate (LVF) is a good example of this type of compounds and a broad spectrum antibiotic of the fluoroquinolone drug class. The samples of LVF with and without grinding were studied using different characterization techniques such as thermogravimetry, differential scanning calorimetry, fourier-transformed infrared, X-ray powder diffraction, and hot stage microscopy. The purpose of the present study was to evaluate the effects of grinding in the dehydration and rehydration processes in levofloxacin hemihydrate. After heating, the samples lost water molecules and the rehydration process was modified depending on defects due to the grinding. At room temperature, the complete transformation to the hemihydrate form was detected only for the sample without grinding. On the other hand, the milled sample showed two phases, hydrate and anhydrate forms. Therefore, the defects in the crystalline structure would cause the irreversible transformation.